Effect of Vetiveria zizanioides Essential Oil on Melanogenesis in Melanoma Cells: Downregulation of Tyrosinase Expression and Suppression of Oxidative Stress. (19th March 2014) - Peng, Hsin-Yi; Lai, Chin-Chun; Lin, Chih-Chien; Chou, Su-Tze
Abstract : The major objective of this study was to estimate the hypopigmentation function of the essential oil from Vetiveria zizanioides (VZ-EO). Our results indicated that VZ-EO exhibits potent lipid peroxidation inhibitory activity to moderate the bleaching of β -carotene and to maintain the cellular glutathione (GSH) levels. VZ-EO can markedly decrease melanin production and tyrosinase activity in α -melanin-stimulating-hormone- ( α -MSH-) stimulated B16 cells. The effect of VZ-EO on melanogenesis is achieved by the suppression of cellular tyrosinase expression. The results demonstrated that the activity of VZ-EO on melanogenesis might be the result of its potent antioxidative ability, which was reflected in the decreased cellular oxidant and malondialdehyde (MDA) levels and the recovered activities of superoxide dismutase (SOD), glutathione peroxidase (GPX), and catalase (CAT) in α -MSH-stimulated B16 cells. The most abundant compound in VZ-EO is cedr-8-en-13-ol (12.4%), which has a strong capability to inhibit lipid peroxidation. Therefore, VZ-EO has the potential to become an ingredient in future hypopigmentation drugs, foods, and cosmetics.